Ontology evaluation - A criteria selection framework - Hooi, Y.K. (Institute of Electrical and Electronics Engineers Inc., 2016)
A complete ontology does not contain all domain information yet may still meet the requirements. Evaluation of ontology is necessary to determine the quality. To evaluate the quality of an ontology, various criteria have been proposed. This paper is a tribute to the works done through comparative study with the goal of identifying overlaps and establishing relationship of the various criteria. A framework is proposed to guide the choice of suitable criteria for various ontology evaluation levels and evaluation methods. Â© 2015 IEEE.